Activity concentration of terrestrial and anthropogenic radionuclides (226Ra, 222Rn, 232Th, 40K, and 137Cs) in soil samples - Altıkulaç, Aydan; Turhan, Şeref; Gümüş, Hasan (Springer Science and Business Media LLC, 2015)
Measurement of the activity concentrations of terrestrial and anthropogenic radionuclides in one hundred fifteen soil samples collected from various locations in Samsun city was taken using a gamma-ray spectrometer with a NaI (Tl) detector. The average activity concentrations of terrestrial radionuclides 226Ra, 232Th, and 40K were measured as 38.1 ± 1.4, 39.3 ± 0.8, and 375.3 ± 10.2 Bq kg−1, respectively. The average activity concentration of anthropogenic radionuclide 137Cs measured in some soil samples was found as 12.1 ± 0.7 Bq kg−1. Radon concentrations in soil and in air were estimated using results of the measurement of activity concentrations of 226Ra. The average concentrations of radon in soil and air were found as 32 kBq m−3 and 101 Bq m−3, respectively. The absorbed gamma dose rate in outdoor air due to terrestrial radionuclides in soil samples varied from 28 to 95 nGy h−1 with an average of 57 nGy h−1. The annual effective dose rates caused from external and inhalation exposure were estimated as 70 and 958 μSv y−1, respectively.
Keywords: 13. Climate action; 11. Sustainability; 7. Clean energy